2012
DOI: 10.1111/j.1540-8183.2012.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Deformation of Contemporary Coronary Stents: An Integrated Analysis of Clinical Experience and Observations from the Bench

Abstract: In our practice LSD was a rare observation only seen with the Promus Element stent. When subjected to longitudinal compression in a bench test all contemporary stents can be compressed. Compression of Promus Element occurs at a lower force, but it is the only stent where deformations are detected with x ray. Postdilatation can partially improve LSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 9 publications
1
23
1
Order By: Relevance
“…A quantitative definition of LSD by QCA could have detected hidden LSD cases in less radio-opaque stents, such as Xience, Resolute, or Biomatrix, which were difficult to detect via visual examination of angiography. 18 In line with these results, an IVUS analysis also reported that the incidence of LSD was similar among various types of second-generation DES. 19 These findings suggest that factors other than the stent platform itself, such as lesion or procedural factors, may have had a greater impact on the occurrence of QCA-based LSD.…”
Section: Rhee Et Al Risk Factors Of Longitudinal Stent Deformationsupporting
confidence: 62%
“…A quantitative definition of LSD by QCA could have detected hidden LSD cases in less radio-opaque stents, such as Xience, Resolute, or Biomatrix, which were difficult to detect via visual examination of angiography. 18 In line with these results, an IVUS analysis also reported that the incidence of LSD was similar among various types of second-generation DES. 19 These findings suggest that factors other than the stent platform itself, such as lesion or procedural factors, may have had a greater impact on the occurrence of QCA-based LSD.…”
Section: Rhee Et Al Risk Factors Of Longitudinal Stent Deformationsupporting
confidence: 62%
“…A previous IVUS study found that the incidence of malapposition after DES deployment was 7.2% overall, and 34.3% in patients with acute myocardial infarction . Post‐balloon dilatation to resolve stent malapposition might cause longitudinal stent elongation, a type of longitudinal stent deformation, which could cause major complications . Although the clinical implications of stent malapposition are controversial, some lesion characteristics, such as calcification and severe diameter stenosis, have been reported to be predictive of acute stent malapposition that occurs during a PCI procedure …”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal stent deformation, which is defined as the distortion of a stent in the longitudinal axis,1‐3 is a relatively common stent complication during percutaneous coronary intervention (PCI) procedures . Longitudinal stent deformation has been reported to cause major complications including stent thrombosis, emergency coronary artery bypass graft, and death, which accounts for 7% and 14% of cases in two reports from the MAUDAE complication database . Although longitudinal stent deformation is mainly described as focal or overall longitudinal stent shortening, some recent case reports have also described the occurrence of longitudinal stent elongation as a type of longitudinal stent deformation .…”
Section: Introductionmentioning
confidence: 99%
“…[4567] The majority of LSD affects the proximal aspect of the stent and is due to attempts to withdraw secondary equipment, most commonly an IVUS catheter, filter wire device, and previously inflated balloon.…”
Section: Discussionmentioning
confidence: 99%